Recombinant Haemagglutinin Derived From the Ciliated Protozoan Tetrahymena thermophila Is Protective Against Influenza Infection - Jawinski, Karina; Hartmann, Marcus; Singh, Charanjit; Kinnear, Ekaterina; Busse, David C.; Ciabattini, Annalisa; Fiorino, Fabio; Medaglini, Donata; Trombetta, Claudia Maria; Montomoli, Emanuele; Contreras, Vanessa; Le Grand, Roger; et al. (Frontiers in Immunology, 2019)
Current influenza vaccines manufactured using eggs have considerable limitations, both in terms of scale up production and the potential impact passaging through eggs can have on the antigenicity of the vaccine virus strains. Alternative methods of manufacture are required, particularly in the context of an emerging pandemic strain. Here we explore the production of recombinant influenza haemagglutinin using the ciliated protozoan Tetrahymena thermophila. For the first time we were able to produce haemagglutinin from both seasonal influenza A and B strains. This ciliate derived material was immunogenic, inducing an antibody response in both mice and non-human primates. Mice immunised with ciliate derived haemagglutinin were protected against challenge with homologous influenza A or B viruses. The antigen could also be combined with submicron particles containing a Nod2 ligand, significantly boosting the immune response and reducing the dose of antigen required. Thus, we show that Tetrahymena can be used as a manufacturing platform for viral vaccine antigens.